(untitled) (Research, Society and Development, 2024)
Obesity has become a serious global public health problem, affecting an increasingly younger portion of different socioeconomic groups. In addition to being a risk factor for other non-communicable chronic diseases, obesity prevention and weight loss are not straightforward, being associated with physiological processes that hinder weight loss and promote weight gain. Among these processes, a strong presence of insulin resistance is observed, characterized by decreased cellular responses to the insulin hormone, which affects the transport of plasma glucose into cells and reduces its efficiency in glycemic control. This study revealed a consensus among the authors that weight loss can significantly improve insulin sensitivity and other associated metabolic parameters, noting a relationship between excessive carbohydrate consumption and increased fat accumulation, but without presenting a consensus on the best dietary composition aimed at improving insulin sensitivity. Therefore, this review aimed to analyze the influence of excess adiposity on the development of insulin resistance, analyzing the impact of different dietary compositions on improving insulin sensitivity, also investigating how insulin resistance itself impacts fat gain, and outlining strategies for reducing the hormone resistance levels. A literature review was conducted using international articles from the PubMed database, with inclusion criteria of articles published in the last ten years and clinical trials.